Direct model reference adaptive control of coupled tank liquid level control system - Mahyuddin, Muhammad Nasiruddin (2005)
Industries such as petro-chemical industries, paper making industries, waste management and others are the vital industries where liquid level and flow control are essential. Liquids will be processed by chemical or mixing treatment in the tanks, but always the level fluid in the tanks must be controlled, and the flow between tanks must be regulated in the presence of nonlinearity and inexact model description of the plant. This project investigates the usage of Direct Model Reference Adaptive Control (DMRAC) in controlling the liquid level in the second tank of Coupled-Tank plant through variable manipulation of water pump in the first tank. It is to show that DMRAC could produce appropriate control signal to the coupled-tank system in response to the given desired water level with plant nonlinearity and measurement noise present simultaneously. The ability to use only input-output measurement of the plant in adaptation mechanism is the DMRAC’s special characteristics that does not require the explicit identification of the model description nor the solution to linear(or nonlinear) equations of the respective plant dynamics. A dynamic model of the plant is initially developed. Simulation studies are then conducted based on the developed model using Matlab and Simulink. A series of tracking performance tests, disturbance rejection and plant parameter changes are conducted to evaluate the controller performance in comparison to PID controller. The outcome of the project reveals that DMRAC is more robust than PID controller when there is a change in system parameters despite of its sensitivity to measurement noise. The framework of this project is generic enough to have an overview of the possible outcome before implementing the DMRAC controller in real-time system in the future.